2007
DOI: 10.1002/biot.200700105
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, values, and socio‐demographic characteristics that predict acceptance of genetic engineering and applications of new technology in Australia

Abstract: Studies of community reactions to biotechnology and genetic engineering (GE), in particular, have identified a number of correlates of acceptance, including the field of application of a technology and various characteristics of the perceiver. Factor analysis of acceptability ratings (N=686) of 12 applications of new technologies revealed three factors, denoting medical, societal, and indulgent applications. Acceptability ratings of each application and of GE in principle were regressed onto 18 demographic, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
9
18
0
Order By: Relevance
“…Moreover, Onyango and Govindasamy (2004) and Lusk et al (2002) found that despite the US consumer general negative attitude toward GM technology, the direct health, environmental, and production-related benefits had a positive effect on consumer acceptance of GMF. Similar results were evidenced for Australian consumers (Mohr et al, 2007). From the economic perspective, in the UK (Spence and Townsend, 2006), New Zealand (Knight et al, 2005) and the US (Qin & Brown, 2008), it is found that when consumers perceive price benefits, they are more likely to purchase GMF.…”
Section: Benefit Perceptions Of Gmfsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, Onyango and Govindasamy (2004) and Lusk et al (2002) found that despite the US consumer general negative attitude toward GM technology, the direct health, environmental, and production-related benefits had a positive effect on consumer acceptance of GMF. Similar results were evidenced for Australian consumers (Mohr et al, 2007). From the economic perspective, in the UK (Spence and Townsend, 2006), New Zealand (Knight et al, 2005) and the US (Qin & Brown, 2008), it is found that when consumers perceive price benefits, they are more likely to purchase GMF.…”
Section: Benefit Perceptions Of Gmfsupporting
confidence: 84%
“…The reason for this difference was that the Italian consumers had a more positive attitude toward technology than other EU nations. The supportive results were found in studies in the EU (Gaskel et al, 2004;Siegrist, 2003;Lahteenmaki et al, 2002) and Australia (Mohr et al, 2007). Concerning developing nations, similar findings were evidenced in Malaysia that consumer attitude toward modern technology has a positive relationship with consumer support for the GM soybean (Amin et al, 2006).…”
Section: Attitude Toward Modern Technologysupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, cluster group 3, characterised as more concerned about the safety of technology, predominantly focused on the source of LCO3FA, with other attributes such as the type of product and labelling being of lesser concern. Notably, they also gave greatest relative utility to the food regulator (FSANZ) in contrast to the other cluster groups, who gave higher utilities to other sources of information (Government science agency and, particularly the National Heart Foundation) that have previously been found to be trusted and credible (Mohr et al, 2007;Noakes & Crawford, 1991).…”
Section: Overallmentioning
confidence: 95%
“…For example, our laboratory (CSIRO, a government science agency) is known to be trusted and have credibility (Cormick, personal communication;Mohr, Harrison, Wilson, Baghurst, & Syrette, 2007) in certain contexts. We also wanted to know if the national food regulator (Food Standards Australia New Zealand, FSANZ) would also be perceived as trustworthy and credible, as, unlike the USA where the FDA is well known (Rowlands & Hoadley, 2006), FSANZ has an unknown public profile.…”
Section: Choice Of Attributesmentioning
confidence: 98%